Majlis penyubur iman menurut Ibnu Qasyyim Al-Jariyah ; penerjemah, Muqimuddin Shaleh ; editor, Saiful Bahri - Ali Bin Muhammad bin Sulaiman Ad-Dahamy; Shaleh, Muqimuddin; Bahri, Saiful (1994)
155 hlm 13 cm